2004
DOI: 10.1007/s00216-003-2226-1
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of isotope ratios on transient signals by MC-ICP?MS

Abstract: Precise and accurate isotope ratio measurements are an important task in many applications such as isotope-dilution mass spectrometry, bioavailability studies, or the determination of isotope variations in geological or nuclear samples. The technique of MC-ICP-MS has attracted much attention because it permits the precise measurement of isotope compositions for a wide range of elements combined with excellent detection limits due to high ionisation efficiencies. However, the results are based mainly on measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 18 publications
0
34
0
Order By: Relevance
“…4f, Table 2). Several studies involving transient signal processing have shown that isotope ratios derived from rapidly rising or decreasing signals can be affected by delayed Faraday amplifier response times (e.g., [51,59,66,67]). The decreased precision of the spot analysis shown in Figure 4f might contain a contribution of this effect.…”
Section: Precision Accuracy Spatial Resolution and Materials Consummentioning
confidence: 99%
“…4f, Table 2). Several studies involving transient signal processing have shown that isotope ratios derived from rapidly rising or decreasing signals can be affected by delayed Faraday amplifier response times (e.g., [51,59,66,67]). The decreased precision of the spot analysis shown in Figure 4f might contain a contribution of this effect.…”
Section: Precision Accuracy Spatial Resolution and Materials Consummentioning
confidence: 99%
“…As regards Sr, two problems persisted: the Sr-Rb separation and, more generally, the difficulty of the multi-collector to measure a transient signal, typical of ICP-MS, with high precision. With the use of MC-ICP-MS as a chromatographic detector and by coupling it with a liquid chromatograph, the first hyphenated systems dedicated to the measurement of isotopic ratios were obtained [23]. More recently, and just for the purpose of the determination of the 87 Sr/ 86 Sr isotopic ratio, an online Rb-Sr separation procedure has been tested and optimized, using ion chromatography coupled with MC-ICP-MS [24].…”
Section: Ion Chromatography Separationmentioning
confidence: 99%
“…13 The MC-ICP-MS allows measurement of up to 9 masses within a 17% mass range simultaneously using Faraday cups. The fixed centre cup can be switched from Faraday to ion counter.…”
Section: Instrumentationmentioning
confidence: 99%